Association between phenotypic familial hypercholesterolaemia and telomere length in US adults: results from a multi-ethnic survey. (28th August 2018) - Banach, Maciej; Mazidi, Mohsen; Mikhailidis, Dimitri P; Toth, Peter P; Jozwiak, Jacek; Rysz, Jacek; Watts, Gerald F
Abstract: Aims: Familial hypercholesterolaemia (FH) accelerates atherosclerotic cardiovascular disease (ASCVD) and accordingly is the most potent hereditary cause of premature coronary heart disease. The association between telomere length (TL), a biological index of ageing, and FH has not been hitherto investigated. We addressed this question using data from the US National Health and Education National Surveys (NHANES, 1999–2002). Methods and results: We included individuals, who had TL measurements (with quantitative polymerase chain reaction method) and a phenotypic diagnosis of FH based on the Dutch Lipid Clinic Network (DLCN) criteria. Sample weights were applied for unequal probabilities of selection, non-response bias, and oversampling by complex sample analysis. The adult prevalence of FH in NHANES was 0.43% [95% confidence interval (95% CI) 0.33–0.57]. The frequencies of probable FH (mean DLCN score: 6.2) and definite FH (mean DLCN score: 8.9) were 0.42% (95% CI 0.32–0.48) and 0.03% (95% CI 0.02–0.06), respectively. Subjects with FH had a higher prevalence of non-communicable diseases (hypertension, diabetes 2 type, and obesity) and early atherosclerosis (2.9% in overall population vs. 42.2% in FH). Overall, the mean TL in the non-FH population was 1.09 (95% CI 1.06–1.12) (T/S ratio) and 1.09 (95% CI 1.03–1.12) [(T/S ratio) for total FH]. Telomere length adjusted for age, sex, race, and body mass index was shorter in FH compared with healthy subjects (FH 0.89, 95% CI 0.84–0.93 vs. healthy: 1.05, 95% CI 0.97–1.11 T/S ratio; P < 0.001). Subjects with longer TL (highest quartile) had 12% less chance of having FH compared with those with TL in the lowest quartile (Q1, 95% CI 0.78–0.93). Conclusions: These preliminary data suggest an association between TL, an index of biological age, and the presence of FH, the most common inherited cause of premature ASCVD. Given our relatively low sample size, the findings need confirmation in larger studies.